German Ideologies Since 1945
IX, 252 p.
Keywords: The contributors of this volume seek to answer such questions as: 'How did the Germans overcome 'Germanic Ideology', or did they?' 'Why is there no libertarianism in Germany?' 'What do German conservatives wish to conserve?'. Emphasizing shared patterns of thought, the contributors trace the contours of political thought in a divided nation with a difficult past, and ion the shadow of the culture and political values of the United States.